Identification of proliferative progenitors associated with prominent postnatal growth of the pons - Robert A. Lindquist (Nature Portfolio, 2016)
Postnatal growth of the pons is not well characterized. Here the authors show that growth of the murine pons is fastest during postnatal day 0–4, a period preceding myelination, and is primarily driven by an expansion of the oligodendrocyte population that derive from Sox2+Olig2+progenitors.